Diffusion and Effects of Cyber-Crime in Developing Economies. - Kshetri, Nir (Third World Quarterly, 2010)
Cyber-crime's footprints across the developing world are getting bigger. The aim of this article is to examine the structure of cyber-crimes in developing economies. Its central idea is that economic and institutional factors facing cyber-criminals and potential victims in the developing world are different from those in the developed world. In economies characterised by low internet penetration rates and few resources devoted to fighting cyber-crimes, formal institutions related to such crimes tend to be thin and dysfunctional. A cyber-criminal is less likely to be stigmatised in such economies. Moreover, organisations' and individuals' technological and behavioural defence mechanisms are likely to be weaker. Many people in developing economies are also attracted into cyber-crime because of high unemployment and low wages.